Heterogeneous Catalysis and Advanced Oxidation Processes (AOP) for Environmental Protection (VOCs Oxidation, Air and Water Purification) (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The recent developments in the environmental applications of heterogenous catalysis and photocatalysis are described in this book, focusing on air and water purification using innovative and performing catalysts and applying new green and sustainable processes.